Pacing in sport and exercise. A psychophysiological perspektive - Edwards, A.; Polman, R. (Nova Science Publishers, 2012)
Pacing in sport and exercise: a psychophysiological perspective is the first book which comprehensively examines the way humans pace exercise and sporting activities. This concept represents an exciting opportunity to combine the latest physiological and psychological theories with practical sport and exercise applications. The book will be an essential read for sport and exercise science academics, students, coaches, athletes and general exercise enthusiasts.